THE ASSOCIATION OF PROCALCITONIN, LACTATE, WBC COUNT, AND INTERLEUKIN-10 MAY BE HELPFUL IN THE EARLY DIAGNOSIS OF SEPSIS IN BRAZILIAN PATIENTS - Menezes, Cristiane Alves da Silva; Gomes, Victor Hugo Ferreira; Freitas, Fernanda Rocha de; Gonçalves, Simone Martins; Azevedo, Pâmela Santos; Reis, Edna Afonso; Silva, Ieda de Fátima Oliveira; Mota, Ana Paula Lucas (Arquivos de Ciências da Saúde da UNIPAR, 2025)
Introduction: Sepsis is a set of clinical symptoms resulting from inflammation and infection. Several biomarkers are used for early diagnosis and improved management of sepsis. Objectives: This study evaluated the performance of procalcitonin (PCT), interleukin-10 (IL-10), interleukin-6 (IL-6), and classic inflammatory markers in hospitalized patients with suspected sepsis. Sixty-one patients were assessed. The participants were monitored over a three-day period: baseline (Day 0, D0), 24 hours (Day 1, D1), and 48 hours (Day 2, D2). The hospital’s clinical team classified them as “sepsis” or “non-sepsis”. Results: On the first day (D0), PCT, lactate, leukocyte count, IL-10, and IL-6 were elevated in patients with sepsis compared to those without. On Day 1, all of these biomarkers remained elevated in the sepsis group except for IL-6. By Day 2, none of the parameters differed between the sepsis and non-sepsis groups. AUC analyses demonstrated that PCT, lactate, leukocyte count, and IL-10 could discriminate between sepsis and non-sepsis patients, with IL-10 showing the best sensitivity and specificity at D0 and D1. Conclusion: When combined, the biomarkers performed better in diagnosing sepsis in the Brazilian population.